A Comparative Study on Crack-Healing Ability of Al2O3/SiC Structural Ceramic Composites Synthesized by Microwave Sintering and Conventional Electrical Sintering. (22nd June 2021) - Mohankumar, Madhan; Shankar, A. N.; Karthik, T. S.; Saravanakumar, R.; Oruganti, Hemakesavulu; Venkatesa Prabhu, S.; Rakesh, N.
Abstract : This study was conducted to assess and compare the crack-healing ability of conventional electrical sintered and microwave sintered Al2 O3 / x wt. % SiC ( x = 5, 10, 15, and 20) structural ceramic composites. The crack-healing ability of both conventional electrical sintered and microwave sintered specimens was studied by introducing a crack of ∼100 µ m length by Vickers's indentation and conducting a heat treatment at 1200°C for dwell time of 1 h in air. The flexural or bending strength of sintered, cracked, and crack-healed specimens was determined by three-point bending test, and the phase variations by X-ray diffraction and SEM micrographs before and after crack-healing of both the sintering methods were studied and compared. The results show that almost all the specimens recovered their strength after crack-healing, but the strength of microwave sintered Al2 O3 /SiC structural ceramic composites has been shown to be better than that of conventional electrical sintered Al2 O3 /SiC structural ceramic composites. The microwave sintered crack-healed Al2 O3 /10 wt. % SiC specimen shows higher flexural strength of 794 MPa, which was 105% when compared with conventional electrical sintered Al2 O3 /10 wt. % SiC and crack-healed Al2 O3 /10 wt. % SiC specimen. It was found by X-ray diffractogram that before crack-healing, all the conventional electrical sintered samples have SiO2 phase which reduce the crack-healing ability and microwave sintered samples with 15 and 20 wt. % SiC show lesser SiO2 phase and 5 and 10 wt. % SiC samples have no SiO2 phase before crack-healing. However, after crack-healing treatment, all the samples have distinct SiO2 phase along with Al2 O3 and SiC phases. Microwave sintered Al2 O3 /10 wt. % SiC specimen cracks were fully healed which was evident in SEM micrographs.